Telaah Hukum Penitensier Melalui Sistem Pembinaan Narapidana Di Lembaga Pemasyarakatan Di Indonesia - Hani Irhamdessetya (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2023)
Prisoners are no different from other human beings, who at any time make mistakes or negligence in committing unlawful acts. Prisoner is a substitute for the term person punishment or sentence. A perpetrator who commits a criminal offence and has been decided to be convicted by a judge with permanent legal force (in kraht van gewijsde) can be designated as a prisoner. After having the status of an inmate, the inmate can be placed in a correctional institution to receive guidance. Researchers use qualitative research methods using normative juridical methods. Researchers collect data related to the subject or problem according to the researcher. Researchers' data sources come from legal materials such as scientific books, research reports, research journal articles, regulations, scientific works, and other written sources. The results of the study reveal that the existence of correctional institutions is increasingly important, especially in carrying out guidance to prisoners. Therefore, the researcher examines how the function of penitentiary law in the coaching system in correctional institutions and examines how the development of the process of implementing the correctional system according to Law No. 12 of 1995 concerning Corrections.